The Critical Role of Pyroptosis in Peri-Implantitis - Chen L; Tang Z; Fu L; Xie Y; Xu J; Xia H; Xia T; Wang M (Dove Medical Press, 2024)
Liangwen Chen,1,2,* Ziqiao Tang,1,* Liangliang Fu,1 Yang Xie,1 Junyi Xu,1 Haibin Xia,1,3 Ting Xia,3 Min Wang1,3 1State Key Laboratory of Oral & Maxillofacial Reconstruction and Regeneration, Key Laboratory of Oral Biomedicine Ministry of Education, Hubei Key Laboratory of Stomatology, School & Hospital of Stomatology, Wuhan University, Wuhan, People's Republic of China; 2Center for Prosthodontics and Implant Dentistry, Optics Valley Branch, School and Hospital of Stomatology, Wuhan University, Wuhan, People's Republic of China; 3Department of Oral Implantology, School & Hospital of Stomatology, Wuhan University, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Ting Xia; Min Wang, Department of Dental Implantology, School & Hospital of Stomatology, Wuhan University, 237 Luoyu Road, Wuhan, Hubei Province, 430079, People's Republic of China, Email tingzi90s@whu.edu.cn; 83wangmin@whu.edu.cnBackground: Peri-implantitis (PI) is a prevalent complication of implant treatment. Pyroptosis, a distinctive inflammatory programmed cell death, is crucial to the pathophysiology of PI. Despite its importance, the pyroptosis-related genes (PRGs) influencing PI's progression remain largely unexplored.Methods: This study conducted histological staining and transcriptome analyze from three datasets. The intersection of differentially expressed genes (DEGs) and PRGs was identified as pyroptosis-related differentially expressed genes (PRDEGs). Functional enrichment analyses were conducted to shed light on potential underlying mechanisms. Weighted Gene Co-expression Network Analysis (WGCNA) and a pyroptotic macrophage model were utilized to identify and validate hub PRDEGs. Immune cell infiltration in PI and its relationship with hub PRDEGs were also examined. Furthermore, consensus clustering was performed to identify new PI subtypes. Protein-protein interaction (PPI) network, competing endogenous RNA (ceRNA) network, mRNA-mRNA binding protein regulatory (RBP) network, and mRNA-drugs regulatory network of hub PRDEGs were also analyzed.Results: Eight hub PRDEGs were identified: PGF, DPEP1, IL36B, IFIH1, TCEA3, RIPK3, NET7, and TLR3, which are instrumental in the PI's progression. Two PI subtypes were distinguished, with Cluster 1 exhibiting higher immune cell activation. The exploration of regulatory networks provided novel mechanisms and therapeutic targets in PI.Conclusion: Our research highlights the critical role of pyroptosis and identifies eight hub PRDEGs in PI's progression, offering insights into novel immunotherapy targets and laying the foundation for advanced diagnostic and treatment strategies. This contributes to our understanding of PI and underscores the potential for personalized clinical management.Keywords: peri-implantitis, pyroptosis, consensus clustering, immune cell infiltration, regulatory network